The Effect of Catch Volume, Selling Price, and Operating Costs on Fishermen’s Net Income - Aljabir Aljabir; Ega Saiful Subhan; Sumarni Sumarni (Advances in Management & Financial Reporting, 2026)
Purpose: This study aims to analyze the partial and simultaneous effects of catch volume, selling price, and operational costs on the net income of blue swimming crab (rajungan) fishermen. Research Method: A quantitative explanatory approach was employed. Data were collected using Likert-scale questionnaires from 92 active fishermen in Mbawi Village, Dompu Regency, who were selected through probability sampling. The data were analyzed using multiple linear regression. Results and Discussion: Catch volume and selling price have positive and significant effects on net income, whereas operational costs have a negative and significant effect. Simultaneously, these variables account for 71.8% of the variance in income. Implications: Local authorities should implement price-stabilization policies, eliminate oligopsony chains, and provide targeted fuel subsidies. Future studies should explore external factors like weather anomalies and patron-client systems. Originality: This research integrates sociological dimensions into microeconomic profit-margin calculations, offering a comprehensive evaluation of the systemic burdens faced by fishermen amid daily price uncertainties.